KOMUNIKASI INTERPERSONAL KESANTRIAN DALAM MENGATASI SANTRI YANG BERMASALAH DI PONDOK PESANTREN AL-MUSADDADIYAH KABUPATEN GARUT - Nadia Awalliah; Ummu Salamah; Iis Zilfah Adnan (An-Nida : Jurnal Komunikasi Islam, 2024)
Islamic boarding schools are non-formal educational institutions based on Islamic religious education by implementing a dormitory system. In its implementation, of course, there are problems caused by several factors, both internal and external. Therefore, the Santri field was formed as an institution responsible for handling the problems faced by students while at the Islamic boarding school. The purpose of this study is to explain the interpersonal communication carried out by the Santri institution in handling problematic students at the Al Musyaddadiyah Islamic Boarding School, Garut Regency. This study uses a qualitative approach with data collection techniques through observation and interviews. The data is analyzed so that it can explain the role of interpersonal communication carried out by students in handling problematic students. The results of this study indicate that the interpersonal communication process carried out by the Al-Musadaddiyah Islamic Boarding School Santri institution has implemented the dimensions of the principles of interpersonal communication according to Devito, namely openness, empathy, supportive attitudes, positive attitudes and equality.